2017
DOI: 10.1253/circj.cj-16-0916
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of Inferior Vena Cava Parameters for Estimating Right Atrial Pressure in an East Asian Population ― Comparative Simultaneous Ultrasound-Catheterization Study ―

Abstract: Association of Echocardiography. 3,4 However, in the clinical setting, sometimes the invasive RAP and RAP estimated from IVC parameters are not concordant. As a matter of fact, despite the widespread use of the IVC approach for RAP assessment, there are no previous studies that have evaluated this technique in comparison with simultaneous invasive methods. 5-8 There is no report that has compared invasive RAP with simultaneously obtained IVC parameters in a large cohort, and only a few small studies 9-11 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
6
2
Order By: Relevance
“…In our study the results of correlation analysis as well as ROC curve analysis (see Supplementary Tables S2 and S4) argued for choosing IVCin instead of IVCex or IVCcoll as a hemodynamic status predictor. This choice was also consistent with the results of some previous studies showing higher value of IVCin as predictor of elevated right atrial pressure [7,18,32,33].…”
Section: Discussionsupporting
confidence: 91%
“…In our study the results of correlation analysis as well as ROC curve analysis (see Supplementary Tables S2 and S4) argued for choosing IVCin instead of IVCex or IVCcoll as a hemodynamic status predictor. This choice was also consistent with the results of some previous studies showing higher value of IVCin as predictor of elevated right atrial pressure [7,18,32,33].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that sPAPECHO had a detection accuracy that was the same as that of TRPG. Given the inaccuracies of RAP estimation using the ultrasound measurements of the inferior vena cava diameter together with its respiratory variation, [28][29][30] the current guideline recommends using TRPG as the main variable for assessing the echocardiographic probability of PH. 1) However, our results suggest that sPAPECHO using RAP estima-tion according to the current ASE guideline 4) might serve as an accurate screening for PH as TRPG.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we investigated whether the IVCCI and ΔCO values obtained by echocardiography and used for predicting fluid requirements were correlated with one another. In addition, a review of the literature found the IVCCI cutoff value in patients with septic shock was accepted as 40% in terms of response to fluid expansion [1012]. We thus considered the IVCCI cutoff value as 40% and aimed to identify a cutoff value for ΔCO; we also examined whether 1 of these 2 parameters was, based on a clinician’s general experience, sufficient for the diagnosis of hypovolemia in patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…It also reflects the patient’s fluid status [18,19]. Although the literature describes cutoff values ranging from 39% to 42% for the IVCCI in terms of response to fluid expansion [79], the cutoff value of 40% is most commonly reported [1012]. In our study, we considered IVCCI values of 40% or more as hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation